Fault Detection for Wireless Network Control Systems with Stochastic Uncertainties and Time Delays. (27th February 2014) - Zhang, Jie; Guo, Pengfei; Lyu, Ming; Karimi, Hamid Reza; Bo, Yuming
Abstract : The fault detection problem is investigated for a class of wireless network control systems which has stochastic uncertainties in the state-space matrices, combined with time delays and nonlinear disturbance. First, the system error observer is proposed. Then, by constructing proper Lyapunov-Krasovskii functional, we acquire sufficient conditions to guarantee the stability of the fault detection observer for the discrete system, and observer gain is also derived by solving linear matrix inequalities. Finally, a simulation example shows that when a fault happens, the observer residual rises rapidly and fault can be quickly detected, which demonstrates the effectiveness of the proposed method.